Use of Role Playing Method to Improve Student Learning Results in IPS Subject at Class IVA SD Negeri 111 Pekanbaru - Amiati, Amiati (Perspektif, 2018)
Most of the students in elementary school argue that IPS subject matter is a bit difficult to absorb, thus reducing students' motivation to study IPS. Student learning motivation can arise, among others, through a variety of learning methods and fun. One of the learning model that is expected to improve student's learning motivation is role playing learning. From the result of data analysis as a whole can be seen the total number of complete students in IPS lesson is 42 students from 44 students. Student learning completeness also progressed, from 69% to 75%. Completeness is also progressing, from 34.1% to 95.5%. Thus it can be concluded that the application of role playing learning can improve the motivation of students learning grade IVa SD Negeri 111 Pekanbaru.